Podatek rolny jako źródło dochodów własnych gmin - Utzig, Monika (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2007)
In the paper agricultural tax as a source of communal own revenue is presented. The share of agricultural tax in communal own revenue increased in 1999, when communal own revenues increased. Parish were characterized by higher share of agricultural tax in own revenue than municipality. The share was also territorially diverse.